Emotional Engineering, Vol.5 - Fukuda, Shuichi (Springer International Publishing : Imprint: Springer, 2017)
This book provides a review of the latest research on emotion in engineering, with a particular focus on design and manufacturing. Topics include experience, happiness, cognitive science, neuroscience, additive manufacturing, universal design, branding, teamwork. Throughout the book, the emotions of the end users of engineering products are discussed, as well as the perspective of the expert. The book provides researchers, students, and practicing engineers with an opportunity to examine research and practice in engineering from a different perspective, and offers pointers to how to collaborate with people from other fields to help achieve a more connected society. .